Zhou Enlai : the last perfect revolutionary : a biography - Gao, Wenqian, 1953- (PublicAffairs, 2007)
"Zhou Enlai, the premier of the People's Republic of China from 1949 until his death in 1976, is the last Communist political leader to be revered by the Chinese Communist Party. Often touted as "the last perfect revolutionary," he is presented as a modern saint who offered protection to his people during the Cultural Revolution, and an icon that allows modern China to find an admirable figure in what was a traumatic and bloody era." "In China, works about Zhou Enlai are heavily censored, and every hint of criticism removed. When Gao Wenqian first published this work in 2003 in Hong Kong, it was immediately banned in the People's Republic." "In this expanded English edition of that work (which includes additional historical and biographical background on Zhou Enlai and Chinese political history), we are offered an objective portrait of the real Zhou, a man who lived his life at the heart of Chinese politics for fifty years and survived - not thanks to ideological or personal purity, but because he was artful, wily, and politically supple. Although Nixon may have called him "the greatest statesman of our era," Zhou's greatest gift - a result of his acute understanding of where political power resided at any one time - was to survive Mao, Maoism, the Long March, the war against the Nationalists, and the Cultural Revolution." "What emerges from Gao Wenqian's telling is a richly layered portrait of Zhou Enlai, one that offers insight into his relationship with Mao Zedong, and enhances our understanding of modern China."--Jacket